2019
DOI: 10.1155/2019/9704870
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Perspective in Cholangiocarcinoma Diagnostic Process

Abstract: Cholangiocarcinoma is a malignancy arising from the epithelial lining of the intrahepatic or extrahepatic biliary tract. Timely diagnosis is challenging due to its silent clinical course. As reliable laboratory markers are lacking, diagnostic imaging plays a pivotal role. While cross-sectional imaging studies are usually conclusive for intrahepatic lesions, endoscopy plays an essential role in cases of extrahepatic tumors. Rational utilization of different diagnostic methods based on available evidence is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…73 Endoluminal forceps biopsy has been shown to yield greater sensitivity for the diagnosis of CCA from biliary strictures (74%), 74 but compared to brushing, is technically more challenging and may require sphincterotomy. 71 It is worth noting that a metaanalysis including 9 studies showed pooled sensitivity values of 45% for brushing, 48% for biopsies, and an improvement of up to 59% with the combination of both methods. 75 In order to improve the sensitivity, different technical alternatives have been investigated.…”
Section: 2 Endoscopic Approachesmentioning
confidence: 98%
See 3 more Smart Citations
“…73 Endoluminal forceps biopsy has been shown to yield greater sensitivity for the diagnosis of CCA from biliary strictures (74%), 74 but compared to brushing, is technically more challenging and may require sphincterotomy. 71 It is worth noting that a metaanalysis including 9 studies showed pooled sensitivity values of 45% for brushing, 48% for biopsies, and an improvement of up to 59% with the combination of both methods. 75 In order to improve the sensitivity, different technical alternatives have been investigated.…”
Section: 2 Endoscopic Approachesmentioning
confidence: 98%
“…In addition to imaging approaches, invasive techniques such as endoscopic retrograde cholangiography (ERCP), endoscopic ultrasound (EUS), or cholangioscopy are also performed for the histological diagnosis or high-spatial-resolution imaging. 71 ERCP, based on a combination of luminal endoscopy and fluoroscopic imaging, remains the most commonly used method for cytological/histological confirmation of CCA, with a sensitivity and specificity of 74% and 70%, respectively. 72 It enables the…”
Section: 2 Endoscopic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic accuracy of the preoperative mapping of CCA using choledochoscopy requires further validation, owing to the small sample sizes studied[ 73 ]. In a study by Pereira et al [ 74 ] involving 43 patients, the accuracy of DSOC-guided visual impression and DSOC-guided biopsy was 95% and 81% respectively in the diagnosis of CCA.…”
Section: Clinical Applicationsmentioning
confidence: 99%